1999
DOI: 10.1177/026988119901300206
|View full text |Cite
|
Sign up to set email alerts
|

The effects of idazoxan on reaction times, eye movements and the mood of healthy volunteers and patients with upper respiratory tract illnesses

Abstract: An experiment was carried out to determine whether idazoxan, a drug which increases the turnover of central noradrenaline, removes the malaise (reduced alertness, slower psychomotor performance) associated with upper respiratory tract illness (URTI). Eighty-one volunteers were tested when healthy and 17 returned to the laboratory when they developed URTIs. Those who remained healthy were then recalled as a control group. Volunteers were tested before and after receiving either idazoxan (40mg) or a lactose plac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…Previous research has shown that the low alertness state associated with a cold can be reversed by a drug that increases the turnover of central norepinephrine. 16 Indeed, ingestion of caffeine, which increases alertness, has been shown to remove the cold-induced performance impairments seen in laboratory tasks. 17 This suggests that a further study examining whether caffeine can remove the effects found here is required.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that the low alertness state associated with a cold can be reversed by a drug that increases the turnover of central norepinephrine. 16 Indeed, ingestion of caffeine, which increases alertness, has been shown to remove the cold-induced performance impairments seen in laboratory tasks. 17 This suggests that a further study examining whether caffeine can remove the effects found here is required.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of experimentally induced colds have shown that volunteers with colds have impaired psychomotor functioning (poor hand-eye co-ordination, slower response times in reaction time tasks [5,13,14]). Again, these findings have been replicated in studies of naturally occurring colds [15,16,17,18,19,20,21,22,23]. Some studies have used virological assays [20] to ensure that upper respiratory tract infections are being studied.…”
Section: Introductionmentioning
confidence: 89%
“…Secondly, it could reflect neurotransmitter changes produced by immunological responses to the viral infection. Indeed, research suggests that compounds that increase central noradrenaline (e.g., caffeine [18], idazoxan [21]) remove the drowsiness and psychomotor slowing associated with having a cold. People with upper respiratory illnesses have also been found to be more sensitive to other factors that can change alertness (e.g., noise [15]; alcohol [16]; fatigue [22]).…”
Section: Introductionmentioning
confidence: 99%
“…The starting point for this line of research was a study which showed that caffeine removed many of the impairments induced by URTIs (Smith et al, 1997). This led to a study examining whether increases in the turnover of central noradrenaline (produced by the drug idazoxan) could remove the impairments seen in those with a cold (Smith et al, 1999b). The results showed that compounds that increase central noradrenaline may remove the reduced alertness and psychomotor slowing associated with URTIs.…”
Section: Neurotransmitters and Malaisementioning
confidence: 99%